Green Feed Innovation with Goat Milk Yogurt Casein to Mitigate Dioxin Accumulation in Nile Tilapia - Nur Aeni; Sri Magfirah HS (ARRUS Journal of Engineering and Technology, 2025)
Dioxins are toxic and persistent organochlorine pollutants that bioaccumulate in fish tissues, posing health risks to consumers. This study evaluated the potential of casein isolated from goat milk yogurt as a bioprotective agent to reduce dioxin bioaccumulation in Nile tilapia (Oreochromis sp.). A Completely Randomized Design (CRD) was employed with three groups: a negative control (no exposure), a positive control (dioxin exposure), and a therapy group (dioxin exposure plus dietary casein supplementation). Fish were maintained for 30 days, consisting of 15 days of dioxin exposure followed by 15 days of casein therapy. Survival rate was highest in the negative control (100%), intermediate in the therapy group (67%), and lowest in the positive control (17%). Gas Chromatography–Mass Spectrometry (GC–MS) analysis showed that casein supplementation reduced dioxin concentration in muscle tissue threefold compared with the positive control (0.02% vs. 0.06%; p < 0.001). Histopathological analysis further indicated that casein attenuated hepatic damage, with a lower damage score in the therapy group (10) compared to the positive control (16). These findings suggest that casein from goat milk yogurt has potential as a functional feed ingredient to suppress dioxin accumulation and mitigate toxic effects in fish, although full physiological recovery was not achieved.